Ultra compact triplexing filters based on SOI nanowire AWGs - 张家顺 安俊明 赵雷 宋世娇 王亮亮 李建光 王红杰 吴远大 胡雄伟 (Journal of semiconductors, 2011)
An ultra compact triplexing filter was designed based on a silicon on insulator（SOI） nanowire arrayed waveguide grating（AWG） for fiber-to-the-home FTTH.The simulation results revealed that the design performed well in the sense of having a good triplexing function.The designed SOI nanowire AWGs were fabricated using ultraviolet lithography and induced coupler plasma etching.The experimental results showed that the crosstalk was less than -15 dB,and the 3 dB-bandwidth was 11.04 nm.The peak wavelength output from ports a,c,and b were 1455,1510 and 1300 nm,respectively,which deviated from our original expectations.The deviation of the wavelength is mainly caused by 45 nm width deviation of the arrayed waveguides during the course of the fabrication process and partly caused by material dispersion.